2022
DOI: 10.1126/sciadv.abj9424
|View full text |Cite
|
Sign up to set email alerts
|

Chemically induced protein cage assembly with programmable opening and cargo release

Abstract: Engineered protein cages are promising tools that can be customized for applications in medicine and nanotechnology. A major challenge is developing a straightforward strategy for endowing cages with bespoke, inducible disassembly. Such cages would allow release of encapsulated cargoes at desired timing and location. Here, we achieve such programmable disassembly using protein cages, in which the subunits are held together by different molecular cross-linkers. This modular system enables cage disassembly to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…While most protein cage systems to date rely on in vitro packaging of cargo, [88][89][90][91] requiring separate purification as well as disassembly and reassembly steps, our encapsulin-based Dps_Encs can co-package RNA and specific proteins in vivo in a single step. This in situ assembly of functional nanocages simplifies purification and avoids non-physiological in vitro conditions, often necessary for disassembly and cargo loading of other protein nanocages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While most protein cage systems to date rely on in vitro packaging of cargo, [88][89][90][91] requiring separate purification as well as disassembly and reassembly steps, our encapsulin-based Dps_Encs can co-package RNA and specific proteins in vivo in a single step. This in situ assembly of functional nanocages simplifies purification and avoids non-physiological in vitro conditions, often necessary for disassembly and cargo loading of other protein nanocages.…”
Section: Discussionmentioning
confidence: 99%
“…This in situ assembly of functional nanocages simplifies purification and avoids non-physiological in vitro conditions, often necessary for disassembly and cargo loading of other protein nanocages. [88][89][90][91] One challenge of in vivo cargo loading is the potential co-packaging of unwanted molecules, including endogenous RNA and protein. However, the intrinsic specificity of encapsulins for packaging co-expressed TP-tagged proteins has been extensively used to assemble highly homogeneous cargo-loaded cages with minimal non-specific loading.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Heddle et al reported GSH-responsive cross-linkers to cross-link proteins and constructed artificial protein cages with programmable disassembly properties, providing a potentially versatile method for protein delivery. 179 2-Methacryloyloxyethyl phosphorylcholine (MPC) can similarly interact with choline and acetylcholine with nicotinic acetylcholine receptors (nAChRs) and choline transporters (ChTs). Taking advantage of this property, Kang et al used MPC as the monomer, along with the PLA as a crosslinker for successfully treating central nervous system (CNS) diseases.…”
Section: Nanogel For Targeted Antibody Deliverymentioning
confidence: 99%
“…Recently, Heddle et al reported GSH-responsive cross-linkers to cross-link proteins and constructed artificial protein cages with programmable disassembly properties, providing a potentially versatile method for protein delivery. 179…”
Section: Nanogels For Immunomodulatory Therapeuticsmentioning
confidence: 99%
“…, histidine) to ionization can be exploited at a protein–protein interface, with the repulsion of like-charges promoting disassembly. Several studies have demonstrated systems to respond to acidification, mimicking certain viral capsids. , Other studies have exploited disulfide bonds to chemically link protein subunits, conferring stability in oxidizing environments outside the cell but not in intracellular environments, which are typically reducing. Similarly, engineered metal-mediated interactions between proteins can be reversibly broken by chelators of specific metal ions, , though connections to the cell state are less direct. In other studies, control of protein assembly by light and by ligand binding have been explored. , With DNA nanotechnology, a cage opened by ligand binding has been described .…”
Section: Introductionmentioning
confidence: 99%